Design and implementation of a clinical laboratory information system in a low-resource setting - Timothy M. Mtonga (African Journal of Laboratory Medicine, 2019)
Background: Reducing laboratory errors presents a significant opportunity for both cost reduction and healthcare quality improvement. This is particularly true in low-resource settings where laboratory errors are further exacerbated by poor infrastructure and shortages in a trained workforce. Informatics interventions can be used to address some of the sources of laboratory errors.